King of wrath - Ana, Huang (London Piatkus, 2022)
She$1 (Bs the wife he never wanted$1! =(Band the weakness he never saw coming. Ruthless. Meticulous. Arrogant. Dante Russo thrives on control, both personally and professionally. The billionaire CEO never planned to marry$1 (Buntil the threat of blackmail forces him into an engagement with a woman he barely knows. Vivian Lau, jewelry heiress and daughter of his newest enemy. It doesn$1 (Bt matter how beautiful or charming she is. He'll do everything in his power to destroy the evidence and their betrothal. There$1 (Bs only one problem: now that he has her...he can't bring himself to let her go. Elegant. Ambitious. Well-mannered. Vivian Lau is the perfect daughter and her family$1 (Bs ticket into the highest echelons of high society. Marrying a blue-blooded Russo means opening doors that would otherwise remain closed to her new-money family. While the rude, elusive Dante isn't her idea of a dream partner, she agrees to their arranged marriage out of duty. Craving his touch was never part of the plan. Neither was the worst thing she could possibly do: fall in love with her future husband. King of Wrath is a steamy billionaire/arranged marriage romance. It contains explicit sexual content, profanity, and mild violence. Recommended for mature readers only.s